In-Silico Trials for Treatment of Acute Ischemic Stroke - Konduri, Praneeta R.; Marquering, Henk A.; van Bavel, Ed E.; Hoekstra, Alfons; Majoie, Charles B. L. M.; , The INSIST Investigators (Frontiers in Neurology, 2020)
Despite improved treatment, a large portion of patients with acute ischemic stroke due to a large vessel occlusion have poor functional outcome. Further research exploring novel treatments and better patient selection has therefore been initiated. The feasibility of new treatments and optimized patient selection are commonly tested in extensive and expensive randomized clinical trials. As an alternative, in-silico trials, computer-based simulation of randomized clinical trials, have been proposed. In this white paper, we present our vision and approach to set up in-silico trials focusing on treatment and selection of patients with an acute ischemic stroke. The INSIST project (IN-Silico trials for treatment of acute Ischemic STroke; www.insist-h2020.eu) is a collaboration of multiple experts in computational science, cardiovascular biology, biophysics, biomedical engineering, epidemiology, radiology and neurology. INSIST will generate virtual populations of acute ischemic stroke patients based on data from the recent stroke trials and build on the existing and emerging in-silico models for acute ischemic stroke, its treatment (thrombolysis and thrombectomy) and resulting perfusion changes. These models will be used to design a platform for in-silico trials that will be validated with existing data and be used to provide a proof of concept of the potential efficacy of this emerging technology. The platform will be used to evaluate the effectiveness and safety of medication, new thrombectomy device configurations and selection for patient subpopulations for better treatment outcome. In-silico trials allow for rapid hypothesis testing while supporting clinical trial design and hence, can benefit the next generation acute ischemic stroke trials.